A flexible oxygen sensor based on photochromism and a preparation method thereof
Patent Information
- Application Number
- CN202611186439.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-08-06
- Publication Date
- 2026-10-30
AI Technical Summary
[0005]然而,现有的电阻型金属氧化物半导体传感器,工作温度高(室温环境性能差),能耗大,气体的选择性较差,材料的稳定性差
1、工作温度低:本发明的基于光致变色的柔性氧气传感器无需加热装置器件结构简单功耗较低且安全性高。
Smart Images

Figure CN123008763A_ABST
Abstract
Description
Technical Field
[0001] This invention relates to the field of oxygen sensor technology, and more specifically, to a flexible oxygen sensor based on photochromism and its fabrication method. Background Technology
[0002] Oxygen detection is a core technology for assessing life activities, ensuring industrial safety, and monitoring food quality, playing a vital role in biomedical diagnostics, industrial production control, and food packaging and preservation. This technology can achieve qualitative or semi-quantitative analysis of oxygen concentration through electrochemical, optical, or semiconductor sensing principles.
[0003] Among them, resistive metal-oxide-semiconductor (MOS) sensors have been widely studied due to their advantages of simple structure, fast response, and miniaturization. Cerium oxide-based sensors, in particular, have become a research hotspot due to their high oxygen ion conductivity and excellent structural stability. Studies have shown that reducing the electrode gap to the nanoscale can significantly improve the sensor's response speed and sensitivity. The integration of a platinum electrode with a 20-nanometer gap and a cerium oxide thin film enables the sensor to achieve a rapid response of less than ten seconds at relatively low temperatures, shortening the response time by three orders of magnitude compared to traditional micro-gap sensors. Zinc oxide-based resistive sensors have also attracted attention. Undoped zinc oxide thin films prepared by electrochemical deposition can achieve sensitive detection of oxygen without doping, and their response performance is closely related to microstructural parameters such as grain size and orientation factor.
[0004] In industrial process control, fiber optic oxygen sensors occupy an important position due to their characteristics of being resistant to electromagnetic interference and capable of remote measurement. Fiber optic sensors based on phase demodulation technology can extract oxygen concentration information from extremely weak light emission signals and are suitable for puncture detection in confined spaces such as the headspace of metal cans.
[0005] However, existing resistive metal-oxide-semiconductor sensors suffer from high operating temperatures (poor performance at room temperature), high energy consumption, poor gas selectivity, and poor material stability. Fiber optic oxygen sensors, on the other hand, have higher device costs.
[0006] Therefore, the present invention proposes a flexible oxygen sensor based on photochromism, which has important practical significance. Summary of the Invention
[0007] In view of this, the present invention proposes a method for fabricating a flexible oxygen sensor based on photochromism, aiming to solve at least one of the problems in the background art.
[0008] This invention proposes a method for fabricating a photochromic flexible oxygen sensor, comprising the following fabrication steps: Sodium tungstate was dissolved in water by stirring. Concentrated hydrochloric acid was added to the sodium tungstate solution. After the process was completed, the precipitate was separated and washed. The washed precipitate was then added to ethylene glycol and heated and stirred until dissolved to obtain the first mixed solution. The first mixed solution was heat-treated and then cooled to obtain a tungsten oxide quantum dot glycol solution. The tungsten oxide quantum dot ethylene glycol solution and PVA solution were mixed and poured into a mold for ultrasonic dispersion, followed by thermal polymerization treatment. After the process was completed, the mold was removed to obtain a flexible oxygen sensor based on photochromism.
[0009] Preferably, when adding concentrated hydrochloric acid to the sodium tungstate solution, the concentrated hydrochloric acid is added dropwise to the sodium tungstate solution until no more precipitate is formed.
[0010] Preferably, when washing the precipitate, the precipitate is rinsed with deionized water until the pH value of the rinsed deionized water is greater than 3.
[0011] Preferably, the heating temperature for the heating and stirring is 90°C.
[0012] Preferably, the heat treatment temperature is 200°C and the heating time is 48 hours.
[0013] Preferably, the mass fraction of the PVA aqueous solution is 10%, and the volume ratio of the tungsten oxide quantum dot glycol solution to the PVA solution is 1:1.
[0014] Preferably, the temperature of the thermal polymerization treatment is 200°C and the heating time is 48 hours.
[0015] The present invention also proposes a flexible oxygen sensor based on photochromism prepared by the aforementioned preparation method.
[0016] Compared with the prior art, the beneficial effects of the present invention are as follows: 1. Low operating temperature: The photochromic flexible oxygen sensor of the present invention does not require a heating device, has a simple structure, low power consumption, and high safety.
[0017] 2. Excellent detection performance: The photochromic flexible oxygen sensor of the present invention has high detection sensitivity and fast response speed. When it comes into contact with oxygen in the air, the color of the flexible oxygen sensor of the present invention gradually fades from the initial dark blue to light blue, and finally recovers to a light yellow close to the original color after 20 minutes, showing a significant gradient evolution. This allows the present invention to achieve real-time quantitative detection through color change.
[0018] 3. High Selectivity: This invention is based on a reversible redox reaction process with high selectivity. Specifically, when the material is irradiated with ultraviolet light of energy higher than its band gap, valence band electrons are excited to jump to the conduction band, forming electron-hole pairs. The photogenerated electrons in the conduction band can be rapidly converted by W in the crystal lattice. 6+ Ion capture and reduction to W 5+ (or W) 4+ Meanwhile, the holes left by the valence band migrate to the material surface, where they usually react with adsorbed water molecules or hydroxyl groups to generate hydrogen ions (H+). + These H generated on the surface + Subsequently, under the influence of a concentration gradient or electric field, it diffuses into the lattice tunnels of tungsten oxide, combining with the reduced W sites to maintain the charge balance of the system, ultimately forming a colored product called "tungsten bronze" (chemical formula usually represented as H_xWO3). Tungsten bronze contains mixed valence states (W... 5+ / W 6+ Electron transitions between tungsten bronze and hydrogen atoms produce strong broad-spectrum absorption in the visible to near-infrared region, macroscopically manifesting as a change in the material's color from pale yellow or colorless to blue or dark blue. The reverse process, fading, can be achieved by placing the colored material in an oxygen-containing environment. In this environment, oxygen (O2) acts as an electron acceptor, reacting with H+ in the tungsten bronze. + And electrons combine to form water, making W 5+ Re-oxidized to W 6+ H + Once removed from the crystal lattice, the material returns to its initial transparent state. Attached Figure Description
[0019] Various other advantages and benefits will become apparent to those skilled in the art upon reading the following detailed description of preferred embodiments. The accompanying drawings are for illustrative purposes only and are not intended to limit the invention. Furthermore, the same reference numerals denote the same parts throughout the drawings. In the drawings: Figure 1 This is a flowchart illustrating the preparation process of tungsten oxide quantum dots provided in an embodiment of the present invention. Figure 2 A physical image of the flexible oxygen sensor provided in an embodiment of the present invention; Figure 3 The graph shows the evolution of the absorption spectrum of the oxygen sensing film over time (0-20 minutes) under oxygen concentrations of 5%, 10%, 15%, and 21% (air) provided in the embodiments of the present invention. Figure 4 This is a graph showing the color change of a flexible oxygen sensor at different times under an oxygen concentration (5%) provided in an embodiment of the present invention. Detailed Implementation
[0020] Various exemplary embodiments of the present invention will now be described in detail. This detailed description should not be considered as a limitation of the present invention, but rather as a more detailed description of certain aspects, features, and embodiments of the present invention. It should be understood that the terminology used in this invention is merely for describing particular embodiments and is not intended to limit the present invention.
[0021] Furthermore, regarding the numerical ranges in this invention, it should be understood that each intermediate value between the upper and lower limits of the range is also specifically disclosed. Every smaller range between any stated value or intermediate value within a stated range, and any other stated value or intermediate value within said range, is also included within this invention. The upper and lower limits of these smaller ranges may be independently included or excluded from the range.
[0022] Unless otherwise stated, all technical and scientific terms used herein have the same meaning as commonly understood by one of ordinary skill in the art. While only preferred methods and materials have been described herein, any methods and materials similar or equivalent to those described herein may be used in the implementation or testing of this invention. All references to this specification are incorporated by way of citation to disclose and describe methods and / or materials associated with those references. In the event of any conflict with any incorporated reference, the content of this specification shall prevail.
[0023] Various modifications and variations can be made to the specific embodiments described in this specification without departing from the scope or spirit of the invention, as will be apparent to those skilled in the art. Other embodiments derived from this specification will also be apparent to those skilled in the art. This specification and embodiments are merely exemplary.
[0024] The terms “include,” “including,” “have,” “contain,” etc., used in this article are all open-ended terms, meaning that they include but are not limited to.
[0025] like Figure 1 As shown, this invention provides a method for fabricating a photochromic flexible oxygen sensor, comprising the following fabrication steps: Sodium tungstate was dissolved in water by stirring. Concentrated hydrochloric acid was added to the sodium tungstate solution. After the process was completed, the precipitate was separated and washed. The washed precipitate was then added to ethylene glycol and heated and stirred until dissolved to obtain the first mixed solution. The first mixed solution was heat-treated and then cooled to obtain a tungsten oxide quantum dot glycol solution. The tungsten oxide quantum dot ethylene glycol solution and PVA solution were mixed and poured into a mold for ultrasonic dispersion, followed by thermal polymerization treatment. After the process was completed, the mold was removed to obtain a flexible oxygen sensor based on photochromism.
[0026] Understandably, the operating temperature is low: the photochromic flexible oxygen sensor of this invention does not require a heating device, has a simple structure, low power consumption, and high safety.
[0027] It is understood that the photochromic flexible oxygen sensor of the present invention has high detection sensitivity and fast response speed. When it comes into contact with oxygen in the air, the color of the flexible oxygen sensor of the present invention gradually fades from the initial dark blue to light blue, and finally recovers to a near-original pale yellow after 20 minutes, showing a significant gradient evolution. This allows the present invention to achieve real-time quantitative detection through color change.
[0028] Understandably, this invention is based on a highly selective reversible redox reaction process; specifically, when a material is irradiated with ultraviolet light at an energy higher than its band gap, valence band electrons are excited to transition to the conduction band, forming electron-hole pairs. The photogenerated electrons in the conduction band can then be rapidly converted by W electrons in the crystal lattice. 6+ Ion capture and reduction to W 5+ (or W) 4+ Meanwhile, the holes left by the valence band migrate to the material surface, where they usually react with adsorbed water molecules or hydroxyl groups to generate hydrogen ions (H+). + These H generated on the surface + Subsequently, under the influence of a concentration gradient or electric field, it diffuses into the lattice tunnels of tungsten oxide, combining with the reduced W sites to maintain the charge balance of the system, ultimately forming a colored product called "tungsten bronze" (chemical formula usually represented as H_xWO3). Tungsten bronze contains mixed valence states (W... 5+ / W 6+ Electron transitions between tungsten bronze and hydrogen atoms produce strong broad-spectrum absorption in the visible to near-infrared region, macroscopically manifesting as a change in the material's color from pale yellow or colorless to blue or dark blue. The reverse process, fading, can be achieved by placing the colored material in a dark place or an oxygen-containing environment. In this case, oxygen (O2) in the environment acts as an electron acceptor, reacting with H+ in the tungsten bronze. + And electrons combine to form water, making W 5+ Re-oxidized to W 6+ H + Once removed from the crystal lattice, the material returns to its initial transparent state.
[0029] In this invention, when adding concentrated hydrochloric acid to the sodium tungstate solution, the concentrated hydrochloric acid is added dropwise to the sodium tungstate solution until no more precipitate is formed.
[0030] In this invention, when washing the precipitate, the precipitate is rinsed with deionized water until the pH value of the rinsed deionized water is greater than 3.
[0031] In this invention, the heating temperature for heating and stirring is 90°C.
[0032] In this invention, the heat treatment temperature is 200°C and the heating time is 48 hours.
[0033] In this invention, the mass fraction of the PVA aqueous solution is 10%, and the volume ratio of the tungsten oxide quantum dot ethylene glycol solution to the PVA solution is 1:1.
[0034] In this invention, the temperature of the thermal polymerization treatment is 200°C and the heating time is 48 hours.
[0035] This invention also proposes a flexible oxygen sensor based on photochromism.
[0036] Example 1 S1. Add 0.05 mol of sodium tungstate to 50 ml of deionized water and stir continuously until completely dissolved. Then add concentrated hydrochloric acid dropwise to the sodium tungstate solution until no more precipitate is formed. Wash the obtained precipitate continuously with deionized water until the pH of the water after washing is greater than 3. Then mix the precipitate with 100 ml of ethylene glycol and heat the mixture at 90°C with continuous stirring until the precipitate is completely dissolved to obtain the first mixed solution. S2. Transfer the first mixed solution to a 200 ml polytetrafluoroethylene reactor, place the reactor in a forced-air drying oven and heat at 200°C for 48 hours. After the reactor is cooled down, a tungsten oxide quantum dot ethylene glycol solution is obtained. S3. Mix the ethylene glycol tungsten oxide quantum dot solution and the 10% PVA aqueous solution at a volume ratio of 1:1 and pour the mixture into a silicone mold. Sonicate the mixture at 70% power for 1 minute to eliminate the bubbles. Then place the mold in an electric oven at 40°C for 10 hours to thermally polymerize the mixture. After demolding, a flexible oxygen sensor based on photochromism is obtained.
[0037] Effect test 1. The photochromic flexible oxygen sensor from Example 1 (such as...) Figure 2 The evolution of its absorption spectrum over time (0-20 minutes) in five different atmospheres (pure N2, and oxygen concentrations of 5%, 10%, 15% and 21% (air)).
[0038] Using the photochromic flexible oxygen sensor prepared in Example 1 as a sample, the film was first pre-irradiated with 365 nm ultraviolet light for 20 min, resulting in photoreduction of the film to form tungsten bronze (HxWO3), which exhibits a deep blue color and a characteristic absorption peak at 770 nm, which is the characteristic wavelength for detection. Using a UV-Vis spectrophotometer, with the X mode (x) set to nanometers in the Cary option, starting at 900 nm and stopping at 450 nm, and the Y mode (y) set to Abs, and the slit height set to full height, the full-band absorption spectrum of the film was collected at 5-minute intervals for different oxygen concentrations and different resting times. For each oxygen concentration, multiple absorption curves evolving over time were continuously recorded.
[0039] The results are as follows Figure 3 As shown, it can be clearly observed that after the pre-colored (blue) flexible oxygen sensor is exposed to an oxygen-containing environment, the characteristic absorption peak at 770 nm in all spectra (corresponding to the colored tungsten bronze H) remains unchanged. x The intensity of WO3 showed a regular decrease over time, macroscopically manifested as the gradual fading of the blue color of the thin film. This phenomenon directly confirms that colored tungsten bronze can be re-oxidized by oxygen, which is the basis for the oxygen sensing function of this invention. It is particularly noteworthy that even at oxygen concentrations as low as 5%, the absorption peak at 770 nm of this invention still showed a significant attenuation, which initially indicates its ability to detect low concentrations of oxygen.
[0040] 2. Place the photochromic flexible oxygen sensor from Example 1 in a 5% oxygen concentration and observe the color change of the sensor at different placement times.
[0041] like Figure 4 As shown, at a low oxygen concentration (5%), although the fading rate is relatively slowed down, a significant color gradient change can still be observed within a 20-minute observation period, demonstrating that the present invention has an effective detection capability for low concentrations of oxygen.
[0042] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of the present invention and not to limit it. Although the present invention has been described in detail with reference to the above embodiments, those skilled in the art should understand that modifications or equivalent substitutions can still be made to the specific implementation of the present invention. Any modifications or equivalent substitutions that do not depart from the spirit and scope of the present invention should be covered within the scope of protection of the claims of the present invention.
Claims
1. A method for fabricating a photochromic flexible oxygen sensor, characterized in that, The preparation steps include the following: Sodium tungstate was dissolved in water by stirring. Concentrated hydrochloric acid was added to the sodium tungstate solution. After the process was completed, the precipitate was separated and washed. The washed precipitate was then added to ethylene glycol and heated and stirred until dissolved to obtain the first mixed solution. The first mixed solution was heat-treated and then cooled to obtain a tungsten oxide quantum dot ethylene glycol solution. The tungsten oxide quantum dot ethylene glycol solution and PVA solution were mixed and poured into a mold for ultrasonic dispersion, followed by thermal polymerization treatment. After the process was completed, the mold was removed to obtain a flexible oxygen sensor based on photochromism.
2. The method for fabricating a photochromic flexible oxygen sensor according to claim 1, characterized in that, When adding concentrated hydrochloric acid to a sodium tungstate solution, add the concentrated hydrochloric acid dropwise into the sodium tungstate solution until no more precipitate is formed.
3. The method for fabricating a photochromic flexible oxygen sensor according to claim 1, characterized in that, When washing the precipitate, the precipitate is rinsed with deionized water until the pH value of the rinsed deionized water is greater than 3.
4. The method for fabricating a photochromic flexible oxygen sensor according to claim 1, characterized in that, The heating temperature for the heating and stirring is 90°C.
5. The method for fabricating a photochromic flexible oxygen sensor according to claim 1, characterized in that, The heat treatment temperature is 200℃, and the heating time is 48h.
6. The method for fabricating a photochromic flexible oxygen sensor according to claim 1, characterized in that, The PVA aqueous solution has a mass fraction of 10%, and the volume ratio of the tungsten oxide quantum dot ethylene glycol solution to the PVA solution is 1:
1.
7. The method for fabricating a photochromic flexible oxygen sensor according to claim 1, characterized in that, The thermal polymerization treatment was carried out at a temperature of 200°C for 48 hours.
8. A flexible oxygen sensor based on photochromism, prepared by the preparation method according to any one of claims 1-7.
